UWB channel measurement and data transfer analysis for multiuser Infostation applications - Nunoo, Solomon (2014)
In this paper, the results of the time dispersion parameters obtained from a set of channel measurements conducted in various environments that are typical of multiuser Infostation application scenarios are presented. The measurement procedure takes into account the practical scenarios typical of the positions and movements of the users in the particular Infostation network. To provide one with the knowledge of how much data can be downloaded by users over a given time and mobile speed, data transfer analysis for multiband orthogonal frequency division multiplexing (MB-OFDM) is presented. As expected, the rough estimate of simultaneous data transfer in a multiuser Infostation scenario indicates dependency of the percentage of download on the data size, number and speed of the users, and the elapse time.